Agmatine an endogenous anxiolytic/antidepressant agent? - ARICIOĞLU, FEYZA (NEW YORK ACAD SCIENCES, 2003)
Agmatine, an endogenous cationic amine, exerts a wide range of biologic effects, but its physiologic role is still to be determined. The aim of the present experiments was to investigate the role of agmatine in anxiety and depression. The forced swim test (FST) and the elevated plus maze (EPM) were used to determine the antidepressant and anxiolytic effects of agmatine in comparison with imipramine (30 mg/kg i.p.). Agmatine (10, 20, 40, 80, or 100 mg/kg, i.p.), saline, or imipramine was given 30 minutes before the tests. Agmatine decreased immobility time in the FST and increased the time spent in the open arms in the EPM, as compared with the saline group. As an endogenous substance, agmatine have modulatory effect on anxiety and depression.
Keywords: agmatine; forced swim test; elevated plus maze; imidazoline; NMDA; nitric oxide; FORCED SWIMMING TEST; CLONIDINE-DISPLACING SUBSTANCE; ELEVATED PLUS-MAZE; NITRIC-OXIDE; RATS; MICE; IMIDAZOLINE; 7-NITROINDAZOLE; INHIBITION; ANXIOLYSIS